Screening for osteoporosis and fracture risk in women with type 1 diabetes. (4th October 2021) - Roberts, Brona; Connolly, Grainne; Lewis, Anthony; Lindsay, John; Loughrey, Clodagh; Nugent, Ailish; Ryan, Kathryn; Todd, Peter; Wallace, Ian
Abstract: We aimed to determine the acceptability and productivity of systematic bone health screening in women with type 1 diabetes aged 50 or over. We offered women aged 50 or over with type 1 diabetes (T1DM) DXA scans to screen for low bone density. We excluded women already on bone treatment or who had had previous scans within the last five years. If the result was completely 'normal' (according to World Health Organization criteria), no further action was taken. If the scan showed osteopenia or osteoporosis, we performed a comprehensive fracture risk assessment to decide on further management. We offered DXA scanning to 58 women, of whom seven declined. Of the 51 women who attended, nine were diagnosed with osteoporosis. A further seven had osteopenia and a combination of other risk factors which warranted bone protection. All these 16 women were either offered osteoporosis treatment immediately or referred to our metabolic bone service. The average age of the women screened was 61.4 years (range 51–85), average body mass index 29.1kg/m 2 (19.2–40.7) and average HbA1c 67.3mmol/mol (43–104). Twelve had stage 3–5 chronic kidney disease. It was concluded screening for fracture risk among women with T1DM is highly acceptable to patients and yields a substantial proportion of women who may benefit from highly cost‐effective bone‐protecting agents. We recommend that centres caring for adults with T1DM consider how bone health assessment could be incorporated into their services, particularly for older female patients who are at high risk of falls and fractures. Copyright © 2021 John Wiley & Sons.